2002
DOI: 10.1266/ggs.77.63
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial telomere-like repeats in the Arabidopsis thaliana genome.

Abstract: Eukaryotic chromosomal ends are protected by telomeres, which are thought to play an important role in ensuring the complete replication of chromosomes. On the other hand, non-functional telomere-like repeats in the interchromosomal regions (interstitial telomeric repeats; ITRs) have been reported in several eukaryotes. In this study, we identified eight ITRs in the Arabidopsis thaliana genome, each consisting of complete and degenerate 300-to 1200-bp sequences. The ITRs were grouped into three classes (class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
59
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 15 publications
3
59
1
Order By: Relevance
“…With regard to these results, Majerová and colleagues referred that: "This is, however, in a clear contradiction to the above mentioned data of Uchida et al [6] which provide an exact content of interstitial genomic regions comprising at least 3 telomeric repeats (to exclude random hits) as 20% of the total number telomeric repeats. Thus, according to genomic data, the ratio between terminal and interstitial telomeric repeats is almost reciprocal to that deduced in [4].…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…With regard to these results, Majerová and colleagues referred that: "This is, however, in a clear contradiction to the above mentioned data of Uchida et al [6] which provide an exact content of interstitial genomic regions comprising at least 3 telomeric repeats (to exclude random hits) as 20% of the total number telomeric repeats. Thus, according to genomic data, the ratio between terminal and interstitial telomeric repeats is almost reciprocal to that deduced in [4].…”
mentioning
confidence: 73%
“…Since Arabidopsis telomeres are composed of perfect telomeric repeat arrays, they remain uncut after digestion with Tru9I. In contrast, ITSs are frequently cut because they are composed of very short arrays of perfect telomeric repeats interspersed with degenerated repeats [4][5][6][7]. When Arabidopsis genomic DNA is digested with Tru9I, resolved on an agarose gel and hybridized with a telomeric probe, most of the signals corresponding to ITSs disappear.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, several studies have reported interstitial localization of telomeric repeats, like that observed in the interstitial region of chromosome 10. Interstitial telomeric sites have been demonstrated to be recombination hot-spots, genome rearrangement breakpoints, and even shown to be functional in several species (Day et al 1998;Hastie and Allshire 1989;Park et al 1992;Tremousaygue et al 1999;Uchida et al 2002). P. ginseng have undergone two major rounds of genome duplications (Choi et al 2013).…”
Section: Discussionmentioning
confidence: 99%